KONTRIBUSI PAJAK DAERAH TERHADAP PENDAPATAN ASLI (STUDI KOMPARASI KABUPATEN JAWA TENGAH) - Nadia Fatimah, 09.05.52.0023; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2013)
The purpose of this study is to investigate and analyze the contribution of the regional tax revenue (PAD) in the province of Central Java. In this study, population and sample all the data used is Hotel and Restaurant Tax, Entertainment Tax, Advertisement Tax, Tax street lighting in 10 (ten) districts of Central Java province from 2008 to 2011. The method of data analysis in this research is a qualitative descriptive statistical analysis. The results showed that the Hotel and Restaurant Tax and Advertisement Tax for 4 (four) years contributed to fluctuate, Hotel and Restaurant Tax Contributions and Advertising Tax largest occurred in 2008 and the lowest contribution occurred in 2010. Entertainment Tax and Tax Street Lighting from year to year that contributed to decline. Had Suggestions the following researchers can add variables such as Parking Tax, Tax Groundwater, swallows nests Tax, Customs Tax Acquisition Rights to Land and Buildings.Keywords: revenue (PAD), Local Taxes